Minnesota in the '70s - Kenney, Dave, 1961- (Book collections on Project MUSE., 2013)
"Minnesota forged an identity during the 1970s that would persist, rightly or wrongly, for decades to come. It was a place of note and consequence--a state of presidential candidates, grassroots activism, civic engagement, environmental awareness, and Mary Tyler Moore. All these subjects and more are covered in this book"--